A case study of reality show: Imam Muda-between intrinsic motivation and extrinsic rewards / Nur Suhaila Mohammed Kamal ... [et al.] - Mohammed Kamal, Nur Suhaila; Md Azri, Sayyidah Atiqah; Tunku Ahmad Mustaffa, Tunku Nor Adila; Ahmad Redzuan, Adam Riyadz; Adbul Raof, Rozaidah
The purpose of this paper is to examine the first Islamic reality show in our country, Imam Muda and the influence of lntrinsic Motivation and Extrinsic rewards towards the participants in the show. Whether, all the participants enrolled for the program from their own internal motivation or based on the rewards that they will get when they win the show. Basically, the reality show is about IO young men age from 18- 27 competing to be a young Imam (Imam muda) the winner will get an amazing set of prize, which is cash of RM20 000, an Apple Laptop, a car worth RM 150 000, an !phone, a scholarship to University of Al-Madinah, a trip to Bandung, an opportunity to perform Umrah, to top that up the winner will also get a job as an Imam in a mosque at the center of the city of Kuala Lumpur. Since Islam is a religion of humility and a very down to earth one, questions have arisen about the rewards. Whether the prizes are relevant to the main cause of the show and whether the contestant are competing for the prizes alone or just to become a better leader or Khalifah of Allah. The methodology of this current research is based on qualitative interview with the participant itself, the producer of the show, the judge of the show and also viewers. The researcher decided to interview this 4 person because of they are the most important person to make this show a successful one. However the current research has a main limitation with regard to the generalization of the convenience findings. All of the data's and finding for this research are concluded in the chapter 4 of this paper.